Methyl-selenium compounds inhibit prostate carcinogenesis in the transgenic adenocarcinoma of mouse prostate model with survival benefit - Wang, Lei (2009)
Chemoprevention of prostate cancer by second-generation selenium compounds in reference to selenomethionine holds strong promise to deal with the disease at the root. Here we used the transgenic adenocarcinoma mouse prostate (TRAMP) model to establish the efficacy of methylseleninic acid (MSeA) and methylselenocysteine (MSeC) against prostate carcinogenesis and to characterize potential mechanisms. Eight-week-old male TRAMP mice (C57B/6 background) were given a daily oral dose of water, MSeA or MSeC at 3 mg Se/kg body weight and were euthanized at either 18 or 26 weeks of age. By 18 weeks of age, the genito-urinary (GU) tract and dorsal-lateral prostate (DLP) weights for the MSeA and MSeC-treated groups were lower than for the control (p<0.01). At 26 weeks, 4 out of 10 control mice had GU weight over 2 g, only 1 out of 10 in each of the Se groups did. The efficacy was accompanied by delayed lesion progression, increased apoptosis and decreased proliferation without appreciable changes of T-antigen expression in the DLP of Se-treated mice and decreased serum IGF-1 when compared to control mice. In another experiment, giving MSeA to TRAMP mice from 10-weeks or 16-weeks of age increased their survival to 50 weeks of age, and delayed the death due to synaptophysin-positive neuroendocrine carcinomas and synaptophysin-negative prostate lesions and seminal vesicle hypertrophy. Wild-type mice receiving MSeA from 10 weeks did not exhibit decreased body weight, GU weight or increased serum ALT than the control mice. Therefore, these selenium compounds may effectively inhibit this model of PCa carcinogenesis.